Reconstruction of a Subtotal Maxillectomy Defect Using a Customized Titanium Implant in a 4-Year-Old Child: An 8-Year Follow-Up Report - Mommaerts, Maurice Yves (Frontiers in Surgery, 2020)
Condition: This case report demonstrates the use of alloplastic reconstruction in young children. Method: A three-dimensionally printed titanium implant was used to reconstruct a subtotal maxillectomy defect in a 4-year-old child. Results: We report an 8-year follow-up. The endoprosthesis was split at the midline to address transverse growth. The main finding is that the stigma surrounding resection and surgical reconstruction in pre-adolescents can be prevented by the use of alloplastic reconstruction based on titanium osseointegration. An additional finding is that shear forces should be prevented at the insertion points of the fixation screws in the facial walls by providing a vertical support for the maxillary/palatal shelves. Lastly, transverse maxillary growth in the circumferential sutures and functional matrix was not hampered by splitting the endo- and exoprostheses in the middle (where the mid-palatal suture would normally be located). Conclusion: Alloplastic reconstruction of maxillectomy defects in childhood can offer a viable temporary solution.